KEHIDUPAN NELAYAN TUNA DI DESA GALALA KECAMATAN MANDIOLI SELATAN KABUPATEN HALAMAHERA SELATAN PROVINSI MALUKU UTARA - Noldi Tomangoko (HOLISTIK, Journal of Social and Culture, 2022)
The potential of fishery resources in North Maluku still has considerable utilization opportunities, especially Tuna Fish. The advantages of Tuna Fish from Indonesia have enormous potential to dominate the international tuna market. The most commonly known species of tuna are Yellowfin, Bluefin and Albacore. The aforementioned potential by fishermen in the Mandioli islands in improving their standard of living. Fishing communities in the Mandioli islands use fishing technology based on traditional fishing methods, namely fishing with rumpon, fishing, trawls and nets, each type of boat / boat. Specifically for tuna fishing, among others, by using tuna fishing gear with rumpon or pontoon fishing aids. Fishing is carried out when the tuna fish are near the surface of the water by following or cutting the path of its movement. The fishing facilities used in operating this hand fishing rod are inboard type boats and pump boat-type boats. The poverty that plagues the lives of fishermen is caused by complex factors in which these factors are not only related to fluctuations in fish seasons, limited human resources, capital and access, and fish merchant networks. The condition of fishermen who have capital difficulties is forced to try to maintain their fishing equipment as much as possible so that it can be used for a longer period of time. Another way is to borrow from fish traders, a way that re-establishes a patron-client bond. Keywords : fisherman, tuna, livelihood